Right Ventricular Dimension is a Predictor of Inhospital Mortality after Surgery in Late Presenting Mitral Valve Disease - Zulfayandi Pawanis; Yan Efrata Sembiring; Oky Revianto Sediono Pribadi; Jeffrey Jeswant Dillon (Biomolecular and Health Science Journal, 2025)
Introduction: Mitral valve disease remains a major global heart-related issue affecting developed and developing countries. This study aimed to report overall mortality and evaluate perioperative factors contributing to postoperative inhospital mortality after isolated mitral valve replacement (MVR). Methods: This research was a retrospective study. The data were collected from patients who underwent primary, isolated, and elective MVR between January 2020 and July 2024. The primary outcome was inhospital mortality, and the secondary outcome was identifying factors associated with postoperative mortality. Receiver operating curve (ROC) analysis with area under the curve (AUC) was performed to identify risk factors and to determine the prognostic values. Results: A total of 81 patients were analyzed (mean age: 45.7 ± 13.2 years; body mass index: 21.8 ± 3.9 kg/m²). Of these, 55 were female, and over half of the patients presented with atrial fibrillation and pulmonary hypertension. Preoperative echocardiography showed left atrial dilatation in 98% of patients. The overall mortality rate was 14.8%. Multiple regression analysis indicated right ventricular diameter at base (RVDB) as a significant predictor of inhospital mortality (hazard ratio = 3.798; 95% confidence interval [CI] 1.150–12.541; P = 0.029). ROC analysis showed that an RVDB 3.05 cm predicted postoperative mortality with fairly good accuracy (AUC 0.769; 95% CI 0.632–0.905; P = 0.004). Conclusion: In patients undergoing MVR for mitral valve disease, the right ventricular diameter at baseline is an independent risk factor for inhospital mortality and may serve as a predictive marker for postoperative mortality.